Pengumpulan Dan Penafsiran Pesan Komunikasi Bisnis - Suhairi Suhairi; Ardhinur Ardhinur; M. Fauzan Effendi Effendi; Rizka Azriani; Sucita Saskya (Universitas Dian Nuswantoro, 2022)
The gathering and interpretation of business communications is an important process in the modern business world. In the ever-evolving digital era, companies must be able to collect and interpret business communication information appropriately to gain valuable insights. First of all, the collection of business communication messages is carried out through data collection techniques and data analysis methods, such as interviews, surveys and content analysis. After the data is collected, the next stage is interpretation. The interpretation of business communication messages is carried out through techniques and tools such as context analysis, language analysis, non-verbal analysis, natural language processing technology, speech recognition technology and social media monitoring tools. This involves using sophisticated algorithms and data analysis techniques to identify information that is valuable and relevant to the company. The main benefits of gathering and interpreting effective business communications are increased understanding of customer needs and wants, development of better marketing strategies, identification of new business opportunities, and improvement of internal business processes. However, there are also challenges associated with the collection and interpretation of business communications. One of the main challenges is the large and complex volume of data. Companies must be able to manage and analyze data on a large scale to get clear results. In addition, privacy and security are also important issues in the collection and interpretation of business communications. The company must ensure that the data collected is kept safe and kept confidential, and complies with applicable privacy regulations. In conclusion, gathering and interpreting business communication messages helps companies understand customer views and feedback, improve communication and business decision making, and achieve better overall business goals. However, companies must also pay attention to challenges related to data management and privacy to ensure the success of this process.